2007
DOI: 10.2308/api.2007.7.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Efficiency: Achieving Productivity Improvements through Environmental Cost Management

Abstract: The purpose of this study is to assess how identifying, tracking, and monitoring environmental costs can assist an agenda adopted to improve environmental performance. We do so by providing a theoretical discussion and contextual model of eco-efficiency that includes cost management as part of its activities. This approach draws on the quality management literature and the Porter hypothesis, which assumes that pollution is a form of technical inefficiency and that properly designed regulations stimulate firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The positive impact of GP on economic performance was in line with the results of [50,61,79,102]. The literature suggests that a supplier transfers the cost reduction benefits to its strategic customer through efforts to make the production process green with less pollution and use of resources, hence a buyer reaps the benefits in its attempt of GP [43,61,92]. IR had a non-significant positive effect on economic performance which was per the studies of [50,61], while results of CC supported the findings of Zhu et al [14], who found a negative effect of CC on economic performance.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The positive impact of GP on economic performance was in line with the results of [50,61,79,102]. The literature suggests that a supplier transfers the cost reduction benefits to its strategic customer through efforts to make the production process green with less pollution and use of resources, hence a buyer reaps the benefits in its attempt of GP [43,61,92]. IR had a non-significant positive effect on economic performance which was per the studies of [50,61], while results of CC supported the findings of Zhu et al [14], who found a negative effect of CC on economic performance.…”
Section: Discussionsupporting
confidence: 66%
“…PLS is a composite based approach and fits better for complex models even with small sample sizes [90,91]. PLS-SEM is considered an appropriate method of analysis when latent variable scores are needed to be used in subsequent analysis, and this method is also recommended if the model contains a higher order construct with only two first-order constructs [47,92]. SmartPLS 3 [93] software was used to examine the validity and reliability of the constructs and their linked manifest variables and test the hypotheses.…”
Section: Non-response Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Products produced under strict ecological and social standards also suffer from fewer process interruptions, which enhances throughput and reduces unit costs of production compared with less sustainable products (Brady et al 1999, Burnett et al 2007). According to the concept of eco-efficiency, firms can produce the same amount with fewer or the same level of resources than traditional methods, which results in decreased costs per purchased item (Gee 1994, Lye, Lee andKhoo 2001).…”
Section: Sustainable Practices Sustainable Supplier Co-operation Andmentioning
confidence: 99%